A study on factors affecting level of job satisfaction among teachers in Kluang, Johor / Alya Najibah Md Hassim and Siti Aishah Selamat - Md Hassim, Alya Najibah; Selamat, Siti Aishah (2022)
The main purpose of this research is to examine the level of job satisfaction among teachers in Kluang, Johor. Based on the objectives, several factors have been identified in influencing teachers’ job satisfaction. Workload, technology, resources and facilities as well as school culture are the factors that assumed to have a relationship with job satisfaction. The data of the study were obtained from 251 respondents through an online survey form. The study was then analyzed by using the Statistical Package for Social Science (SPSS). Four major analyses were tested using Pearson correlation. The study found a significant relationship between workload and job satisfaction (r =.203, p =.001), resources and facilities with job satisfaction (r =.289, p =.000), and school culture with job satisfaction (r =.423, p =.000). The findings also revealed a significant negative relationship between technology and job satisfaction (r = -.126, p =.047). According to the study's findings, all factors influence job satisfaction. Therefore, suggestions have been provided based on all of the factors involved in effort to increase teachers’ job satisfaction. This is due to the fact that teachers are the main catalysts that play the vital role to provide the best services to educate younger generations.